1999
DOI: 10.1038/sj.bmt.1701997
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of pediatric BMT on siblings

Abstract: Summary:Although bone marrow transplantation (BMT) has become standard therapy for many life-threatening disorders of childhood, there is little research on the psychosocial impact of BMT on siblings of children undergoing BMT. Such siblings face issues common to any family with a chronic illness. However, the psychological impact on the family is intensified because two family members, usually children, are subjected to intrusive medical procedures. Investigators had earlier noted that sibling donors may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…The literature has shown that siblings of HSCT patients are at risk of developing emotional reactions such as post-traumatic stress disorder, anxiety, and overall low self-esteem. [31][32][33][34] Pot-Mees and Zeitlin 8 found new behavior problems occurred far more frequently among siblings who were BM donors than among nondonors. See Table 4 for a list of psychosocial reactions specific to siblings.…”
Section: Psychosocial Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has shown that siblings of HSCT patients are at risk of developing emotional reactions such as post-traumatic stress disorder, anxiety, and overall low self-esteem. [31][32][33][34] Pot-Mees and Zeitlin 8 found new behavior problems occurred far more frequently among siblings who were BM donors than among nondonors. See Table 4 for a list of psychosocial reactions specific to siblings.…”
Section: Psychosocial Effectmentioning
confidence: 99%
“…As a result, a considerable portion of parental stress stems from concern involved with the health of not only the patient, but the sibling donor as well. 31 Parents have also expressed concerns regarding the nondonor sibling's psychosocial adjustment. 31 Some other sources of parental stress include relocating to the transplant center, living in two separate households, commuting between the home and the transplant center, concurrently caring for other family members, work-related changes, lengthy hospital stays, financial burdens, parental informed consent for the HSCT procedure, dealing with medication compliance and other medical complications.…”
Section: Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the psychological impact of bone marrow donation among siblings should not be underestimated. 233 Children from DI may remain ignorant of their biological parents. Firstly, it has been traditionally considered as a family matter and left for parents to decide, whether they disclose the conception method to their children or not, even though the legislation would allow to detect donor identity.…”
Section: Assisted Reproductive Technologies and Genetics S Soini Et Almentioning
confidence: 99%
“…14 One important and fairly new aspect of sibling adaptation is the issue of the psychosocial impact of paediatric bone marrow transplantation. 15 Imprecise definitions and a lack of longitudinal studies are identified as deficiencies in current research on siblings' psychosocial well being. 16 In order to obtain more definitive information about the impact of childhood cancer on siblings, we conducted a prospective, controlled follow up study of the siblings of newly diagnosed cancer patients.…”
mentioning
confidence: 99%